The Politics of Shakespeare - Cohen, D. author. aut Link
VIII, 156 p.
Keywords: This book is an attempt to explore Shakespearean drama from the vantage point of the oppressed, invisible, and silent individuals and collectivities constructed in the plays. It examines the ideological apparatuses which produce and naturalise oppression and the political structures through which that oppression is sustained. Derek Cohen is concerned to demonstrate the many ways in which political and personal life, always interdependent, intersect. contradict, and disrupt one another often in the interests of and to the advantage of the dominant social ideology.